Preparation and application of zinc modified sludge-based biochar composite material

By forming dual -metal hydroxide with water talc structures in the sludge, and preparing zinc -modified sludge -based biological carbon composite materials through heat treatment, the problem of high thermal solution temperature and low catalytic performance during sludge treatment and treatment. The efficient reduction, stability and resourceization of sludge are realized, and the efficient removal of organic pollutants.

CN119346096APending Publication Date: 2025-01-24HEFEI UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411574841.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing sludge treatment and disposal technology has defects such as secondary pollution, low product recovery rate or harmful gases, making it difficult to achieve efficient reduction, stabilization and resource utilization of sludge.

Method used

Through the use of the dual -metal hydroxide of the water talian structure through the use of the three -price metal aluminum in the sludge and plus the two -valent metal zinc, the thermal solution temperature of the carbonization of biomass is reduced, and the zinc -modified sludge base organism is prepared by thermal treatment. Carbon composite material.

Benefits of technology

Effectively reduce the thermal solution temperature of biomass carbonization, improve the surface area and catalytic performance of the material, enhance the catalytic oxidation performance of organic pollutants, and realize the resource disposal of sludge and waste water purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346096A_ABST
    Figure CN119346096A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of a zinc modified sludge-based biochar composite material, and belongs to the field of disposal and utilization of waste pollutants. The preparation method comprises the following steps: adding municipal sludge (BS) dry powder into a zinc salt solution according to a certain zinc-aluminum ratio, and fully stirring in a constant-temperature water bath to obtain a uniformly dispersed suspension; dropwise adding alkali liquor into the suspension to control the pH value of the system to be 8-9, continuously reacting for 2 hours, aging for a certain time, filtering, washing and drying to obtain (sludge zinc-loaded aluminum hydrotalcite) ZnAl-LDH (at) BS powder; and loading the obtained ZnAl-LDH-coated BS powder to the surface of a graphite felt, and carrying out heat treatment in a nitrogen atmosphere to obtain the ZnAl-LDO-coated BC composite material. The ZnAl-LDO-coated BC composite material is used as an anode catalyst, a titanium sheet with the same area as the ZnAl-LDO-coated BC composite material is used as a cathode, Na2SO4 is used as an electrolyte, and air oxidation reaction is catalyzed under the driving of a weak electric field, so that an organic pollutant solution with a certain concentration can be completely removed within 2 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of waste pollutant disposal and utilization, and specifically relates to the preparation of a zinc-modified sludge-based biochar composite material and its application in the purification of organic pollutant wastewater. Background Art

[0002] With the development of industry and cities, the scale and treatment capacity of sewage treatment plants are constantly increasing, and the total amount of sludge generated is also increasing year by year. Municipal sludge contains not only a large amount of organic matter, but also rich nitrogen, phosphorus, potassium and trace elements. However, it also contains some harmful substances, such as heavy metals, pathogens, parasite eggs and some difficult-to-decompose organic poisons. The presence of these harmful substances makes the treatment and disposal of municipal sludge complicated. If it is not properly treated, it will cause secondary pollution to the environment after discharge. At present, the treatment and disposal technologies of municipal sludge mainly include landfill, incineration, agricultural value-added, anaerobic digestion to produce biogas and alternative building materials. These disposal technologies have defects such as secondary pollution, low product recovery rate or generation of harmful gases. Therefore, it is of great significance to develop a cost-effective and environmentally friendly sludge treatment and disposal method. The conversion of sludge biochar into high-value-added sludge through high-temperature pyrolysis is a promising way to solve the problem of sludge treatment and disposal.

[0003] Preparing sludge into biochar by pyrolysis carbonization is an effective method to achieve metal element fixation and resource utilization. Usually, the carbon material obtained at a higher pyrolysis temperature (>900°C) is more likely to have higher porosity and stability. However, as the temperature increases, it will lead to higher energy consumption. In order to maintain high porosity and carbonization rate at a lower temperature, a catalyst can be added to promote the pyrolysis process. At the same time, the catalyst can effectively improve the specific surface area and catalytic performance after being combined with sludge-based biochar. Preparing municipal sludge into a high-efficiency catalyst material is an effective way to achieve municipal sludge reduction, stabilization and resource utilization. Summary of the invention

[0004] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing a zinc-modified sludge-based biochar composite material and its application. The present invention utilizes trivalent metal aluminum in the sludge and added divalent metal zinc in situ to form a double metal hydroxide with a hydrotalcite structure on the sludge surface. During the heat treatment process, it not only effectively reduces the pyrolysis temperature of biomass carbonization, but also greatly reduces the preparation cost of the adsorbent. The organic matter in the sludge supports the hydrotalcite during the carbonization process, making it more dispersed and with a larger specific surface area, which significantly enhances the catalytic activity of the electrically assisted catalytic wet air oxidation reaction.

[0005] The preparation method of the sludge-based biochar-supported zinc-aluminum bimetallic oxide composite material of the present invention comprises the following steps: Municipal sludge (BS) dry powder was added to zinc salt solution at a certain zinc-aluminum ratio and fully stirred in a constant temperature water bath to obtain a uniformly dispersed suspension; alkali solution was added dropwise to the suspension to control the pH value of the system at 8-9, the reaction was continued for 2 h and aged for a certain time. After filtration and washing, the filter cake was vacuum dried at 60 °C to obtain ZnAl-LDH@BS powder; the obtained ZnAl-LDH@BS powder was loaded on the surface of graphite felt and heat treated in a nitrogen atmosphere to obtain ZnAl-LDO@BC composite material.

[0006] The sludge dry powder comes from municipal sludge with a moisture content of 80%, which is dried at 105°C to constant weight, crushed and pulverized, and passed through a 100-mesh sieve to obtain BS dry powder. The mass fraction of aluminum in the BS dry powder is 4.0-6.0%, and the mass fraction of carbon is 14.0-16.0%.

[0007] The zinc salt is one or a mixture of zinc chloride, zinc acetate or zinc sulfate, and the concentration of the solution is 1:2 to 1:1 according to the molar ratio of aluminum in the sludge to zinc in the zinc salt.

[0008] The mass concentration of the sludge dry powder in the solution is 40 g / L.

[0009] The temperature of the constant temperature water bath is 60-70° C., and the time for sufficient stirring is more than 6 hours.

[0010] The alkali solution is a mixed solution of sodium carbonate and sodium hydroxide, the molar ratio of sodium carbonate to sodium hydroxide is about 1:4, and the concentration of sodium carbonate is 0.16 mol / L. The aging time after the alkali solution is added is 6 to 12 hours.

[0011] The loading of ZnAl-LDH@BS powder onto the surface of graphite felt is achieved by the following method: first, the ZnAl-LDH@BS powder is ultrasonically dispersed in an aqueous solution containing 2% polyethylene glycol-6000, and then the graphite felt is immersed in the aqueous solution and placed in a shaker at 40°C for oscillation and drying.

[0012] The mass ratio of polyethylene glycol-6000, ZnAl-LDH@BS and graphite felt is 1.5~6: 0.5~2: 5.

[0013] The heat treatment temperature under nitrogen atmosphere is 230~280℃, and the heat treatment time is 2~8 h.

[0014] Application of the zinc-modified sludge-based biochar composite material in the purification of organic pollutant wastewater.

[0015] Specifically, the ZnAl-LDO@BC is used as an anode catalyst to catalyze air oxidation and degrade organic pollutants under the promotion of a weak electric field.

[0016] Furthermore, at room temperature and pressure, in a dual-electrode system, with ZnAl-LDO@BC as the anode catalyst, a titanium sheet of the same area as the cathode, and Na2SO4 as the electrolyte, air is blown into the bottom of the reactor to increase the reaction mass transfer and provide O2. The air oxidation reaction is catalyzed under the drive of a weak electric field, and a certain concentration of organic pollutants can be completely removed within 2 hours.

[0017] The potential of the weak electric field is constant at 1.8 V.

[0018] The concentration of the organic pollutants is ≤25 mg / L, and the air flow rate is 2 L / min.

[0019] The organic pollutants include dyes, phenols or one or more organic substances in the sulfonamide class of drugs.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The present invention in situ utilizes trivalent metal aluminum in municipal sludge and added divalent zinc ions to prepare a sludge-based composite material containing a hydrotalcite structure, thereby greatly increasing the specific surface area of ​​the sludge-based material.

[0021] 2. The addition of zinc ions has a catalytic effect on the pyrolysis of sludge biomass, thereby effectively reducing the pyrolysis temperature of sludge biomass and improving its carbonization efficiency. While saving energy, it also reduces carbon emissions during the pyrolysis process.

[0022] 3. The ZnAl-LDO@BC prepared by the present invention can be used as an anode catalyst material for electrically catalytic wet air oxidation reaction, and can be used for the purification of organic pollutants in wastewater, providing a new idea for the resource disposal of municipal sludge. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD patterns of ZnAl-LDO@BC and ZnAl-LDH@BS prepared under the conditions of Example 1 and the unmodified sludge-based biochar (BC) obtained at the heat treatment temperature of Example 1 as a comparison. It can be seen from the figure that ZnAl-LDH@BS has the characteristic diffraction peak of the hydrotalcite structure (JCPDS22-0700), while the characteristic peak of the hydrotalcite structure of ZnAl-LDO@BC disappears after calcination and is converted into a composite oxide of aluminum oxide and zinc oxide.

[0024] Figure 2 The Raman spectra of ZnAl-LDO@BC and BC prepared under the conditions of Example 1 are shown in Figure 1. -1 It can be seen from the D peak and G peak of carbon that the I D / I GThe value is significantly reduced compared with BC, indicating that the defect degree of biomass carbon material is reduced and the graphitization degree of the material is improved, which is beneficial to the enhancement of the conductivity and catalytic activity of the material.

[0025] Figure 3 The TG (a) and DTG (b) curves of ZnAl-LDH@BS and BS prepared under the conditions of Example 1. It can be seen from the figure that the pyrolysis temperature of biomass in BS starts at 302°C, while the pyrolysis temperature of biomass in ZnAl-LDH@BS is advanced to 221°C, indicating that Zn has a significant catalytic effect on the pyrolysis of biomass, thereby reducing the pyrolysis temperature and saving energy consumption of thermal treatment.

[0026] Figure 4 The nitrogen adsorption-desorption isotherms of BS, ZnAl-LDH and ZnAl-LDH@BS (a) and BC, ZnAl-LDO and ZnAl-LDO@BC (b) under the conditions of Example 1. The specific surface areas of BS, ZnAl-LDH and ZnAl-LDH@BS are 21.13 m 2 / g, 39.28 m 2 / g and 81.70 m 2 / g, and the specific surface areas of BC, ZnAl-LDO and ZnAl-LDO@BC are 50.40 m 2 / g, 81.87 m 2 / g and 126.1 m 2 / g. It can be seen that the organic matter in the sludge supports and disperses the ZnAl-LDH on its surface, avoiding the stacking of ZnAl-LDH and the formation of agglomeration during the heat treatment process, which is beneficial to the increase of the specific surface area of ​​the material. The specific surface area of ​​the material after catalytic pyrolysis is further improved, which is beneficial to the exposure of the active sites on the catalyst surface, thereby improving the catalytic oxidation performance of the material for organic pollutants.

[0027] Figure 5 The following is a comparison chart of the removal efficiency of 25 mg / L bisphenol A at a potential of 1.8 V when the composite materials obtained by loading the same mass of ZnAl-LDO@BC, ZnAl-LDO, and BC on graphite felt of the same size and blank graphite felt were used as catalyst anodes for the electrocatalytic wet air oxidation reaction under the conditions of Example 1. It can be seen that when ZnAl-LDO@BC loaded on graphite felt is used as an electrode catalyst, the removal efficiency of bisphenol A is the highest within 2 hours, reaching 100%. Under the condition of no external potential, ZnAl-LDO@BC only plays an adsorption role, and its maximum adsorption removal of bisphenol A within 120 minutes is only 18.2%.

[0028] Figure 6The effect of ZnAl-LDO@BC calcined at different temperatures under the conditions of Example 1 on the efficiency of catalytic oxidation of bisphenol A. It can be seen that when the calcination temperature is higher than 230°C, the catalytic performance of the prepared ZnAl-LDO@BC remains basically constant. This is mainly because when the temperature is higher than 230°C, the carbonization of biomass in ZnAl-LDH@BS is basically completed, the specific surface area and conductivity increase, and further increasing the temperature does not significantly improve the catalytic activity of the material. Below 230°C, due to insufficient pyrolysis, the catalyst has a small specific surface area and poor conductivity, and cannot play a good catalytic role. Therefore, the addition of Zn can not only serve as a catalyst for low-temperature pyrolysis, saving energy consumption in material preparation, but also catalyze the degradation of organic pollutants. DETAILED DESCRIPTION

[0029] The municipal sludge dry powder comes from municipal sludge with a moisture content of 80%, which is dried at 105°C to constant weight, crushed and pulverized, and passed through a 100-mesh sieve to obtain sludge dry powder. The mass fraction of aluminum in the sludge dry powder is 5.0%, and the mass fraction of carbon is 15.8%.

[0030] Table 1 below shows the composition and content of the main elements in municipal sludge.

[0031]

[0032] The implementation modes of the present invention are described in detail below in combination with some technical solutions. Embodiment 1:

[0033] 2.0 g of sludge powder was weighed and added to 50 mL of aqueous solution containing 1.01 g of zinc chloride to prepare a suspension. The suspension was placed in a constant temperature water bath at 60 °C and stirred for 6 h. A mixed alkaline solution containing 17 g / L anhydrous sodium carbonate and 25.6 g / L sodium hydroxide was added dropwise to keep the pH of the suspension between 8 and 9. The reaction was continued for 2 h and aged for 12 h. After filtration and washing, the filter cake was dried at 60 °C for 12 h to obtain gray-yellow ZnAl-LDH@BS powder.

[0034] According to the mass ratio of polyethylene glycol-6000, ZnAl-LDH@BS and graphite felt of 3: 1: 5, ZnAl-LDH@BS powder was ultrasonically dispersed in an aqueous solution containing 2% polyethylene glycol-6000. The graphite felt was immersed in the aqueous solution and then placed in a shaker at 40°C for oscillation and drying.

[0035] Finally, the graphite felt-supported ZnAl-LDH@BS was heated to 280 °C in a nitrogen atmosphere and kept warm for 2 h to obtain the graphite felt-supported ZnAl-LDO@BC composite material.

[0036] At room temperature and pressure, with ZnAl-LDO@BC supported on graphite felt as the anode, a titanium sheet of the same area as the cathode, and Na2SO4 as the electrolyte, air was blown into the bottom of the reactor at a flow rate of 20 mL / min to increase the reaction mass transfer and provide O2. The air oxidation reaction was catalyzed at a potential of 1.8 V, and the removal rate of bisphenol A solution with a concentration of 25 mg / L could reach 100% within 2 hours. Embodiment 2:

[0037] 2.0 g of sludge powder was weighed and added to 50 mL of aqueous solution containing 0.81 g of zinc acetate dihydrate to prepare a suspension. The suspension was placed in a constant temperature water bath at 70 °C and stirred for 8 h. A mixed alkaline solution containing 17 g / L anhydrous sodium carbonate and 25.6 g / L sodium hydroxide was added dropwise to keep the pH of the suspension between 8 and 9. The reaction was continued for 2 h and aged for 6 h. After filtration and washing, the filter cake was dried at 60 °C for 12 h to obtain gray-yellow ZnAl-LDH@BS powder.

[0038] According to the mass ratio of polyethylene glycol-6000, ZnAl-LDH@BS and graphite felt of 1.5: 0.5: 5, ZnAl-LDH@BS powder was ultrasonically dispersed in an aqueous solution containing 2% polyethylene glycol-6000. The graphite felt was immersed in the aqueous solution and then placed in a shaker at 40°C for oscillation and drying.

[0039] Finally, the graphite felt-supported ZnAl-LDH@BS was heated to 230 °C in a nitrogen atmosphere and kept warm for 8 h to obtain the graphite felt-supported ZnAl-LDO@BC composite material.

[0040] At room temperature and pressure, with ZnAl-LDO@BC supported on graphite felt as the anode, a titanium sheet of the same area as the cathode, and Na2SO4 as the electrolyte, air was blown into the bottom of the reactor at a flow rate of 20 mL / min to increase the reaction mass transfer and provide O2. The air oxidation reaction was catalyzed at a potential of 1.8 V, and the removal rate of sulfamethoxazole solution with a concentration of 25 mg / L could reach 100% within 2 h. Embodiment 3:

[0041] 2.0 g of sludge powder was weighed and added to 50 mL of aqueous solution containing 1.57 g of zinc sulfate heptahydrate to prepare a suspension. The suspension was placed in a constant temperature water bath at 65 °C and stirred for 12 h. A mixed alkaline solution containing 17 g / L anhydrous sodium carbonate and 25.6 g / L sodium hydroxide was added dropwise to keep the pH of the suspension between 8 and 9. The reaction was continued for 2 h and aged for 8 h. After filtration and washing, the filter cake was dried at 60 °C for 12 h to obtain gray-yellow ZnAl-LDH@BS powder.

[0042] According to the mass ratio of polyethylene glycol-6000, ZnAl-LDH@BS and graphite felt being 6: 2: 5, ZnAl-LDH@BS powder was ultrasonically dispersed in an aqueous solution containing 2% polyethylene glycol-6000. The graphite felt was immersed in the aqueous solution and then placed in a shaker at 40°C for oscillation and drying.

[0043] Finally, the graphite felt-supported ZnAl-LDH@BS was heated to 270 °C in a nitrogen atmosphere and kept warm for 3 h to obtain the graphite felt-supported ZnAl-LDO@BC composite material.

[0044] At room temperature and pressure, with ZnAl-LDO@BC supported on graphite felt as the anode, a titanium sheet of the same area as the cathode, and Na2SO4 as the electrolyte, air was blown into the bottom of the reactor at a flow rate of 2 L / min to increase the reaction mass transfer and provide O2. The air oxidation reaction was catalyzed at a potential of 1.8 V, and the removal rate of Congo red solution with a concentration of 25 mg / L could reach 100% within 2 hours.

Claims

1. A method for preparing a zinc-modified sludge-based biochar composite material, characterized in that: BS dry powder was added to zinc salt solution at a certain zinc-aluminum ratio, and the mixture was fully stirred in a constant temperature water bath to obtain a uniformly dispersed suspension; alkali solution was added dropwise to the suspension to control the pH value of the system at 8-9, the reaction was continued and aged for a certain period of time, and after filtration and washing, the filter cake was vacuum dried at 60°C to obtain ZnAl-LDH@BS powder; the obtained ZnAl-LDH@BS powder was loaded on the surface of graphite felt and heat treated in a nitrogen atmosphere to obtain a ZnAl-LDO@BC composite material.

2. The preparation method according to claim 1, characterized in that: The BS dry powder comes from municipal sludge with a moisture content of 80%. It is dried at 105° C. to constant weight, crushed and pulverized, and passed through a 100-mesh sieve to obtain BS dry powder. The mass fraction of aluminum element in the BS dry powder is 4.0-6.0%, and the mass fraction of carbon element is 14.0-16.0%.

3. The preparation method according to claim 1, characterized in that: The zinc salt is one or a mixture of zinc chloride, zinc acetate or zinc sulfate, and the concentration of the solution is 1:2 to 1:1 according to the molar ratio of aluminum in the sludge to zinc in the zinc salt.

4. The preparation method according to claim 1, characterized in that: The alkali solution is a mixed solution of sodium carbonate and sodium hydroxide, and the molar ratio of sodium carbonate to sodium hydroxide is 1:

4.

5. The preparation method according to claim 1, characterized in that: The ZnAl-LDH@BS powder was loaded onto the graphite felt surface by the following method: the ZnAl-LDH@BS powder was first ultrasonically dispersed in an aqueous solution containing 2% polyethylene glycol-6000, and then the graphite felt was immersed in the aqueous solution and placed in a shaker at 40°C for oscillation and drying.

6. The preparation method according to claim 5, characterized in that: The mass ratio of polyethylene glycol-6000, ZnAl-LDH@BS and graphite felt is 1.5~6: 0.5~2:

5.

7. The preparation method according to claim 1, characterized in that: The heat treatment temperature under nitrogen atmosphere is 230~280℃, and the heat treatment time is 2~8 h.

8. Use of the zinc-modified sludge-based biochar composite material prepared according to any one of the preparation methods of claims 1 to 7 in the purification of wastewater with organic pollutants.

9. The use according to claim 8, characterized in that: At room temperature and pressure, in a dual-electrode system, ZnAl-LDO@BC is used as the anode catalyst, a titanium sheet of the same area is used as the cathode, and Na2SO4 is used as the electrolyte. Air is blown into the bottom of the reactor to increase the reaction mass transfer and provide O2. The air oxidation reaction is driven by a weak electric field to degrade and remove organic pollutants.

10. The use according to claim 9, characterized in that: The organic pollutants include dyes, phenols or one or more organic substances in the sulfonamide class of drugs.

Citation Information

Cited By

  • ZnAl-LDH-based material, preparation method thereof and application of ZnAl-LDH-based material in sludge treatment

    CN121085311A